Enhancement of Tech-Sil25 Maxillofacial Silicone Mechanical Properties after Artificial Weathering through Addition of Nanoparticles - Shahad Fadhil Bunyan; Fatanah Mohamad Suhaimi; Faraedon Mohidden Mostafa Zardawi; Siti Noor Fazliah Mohd Noor; Muhammad Azrul Zabidi (International Journal of Dentistry)
Purpose. To evaluate the effect of nanosilica and nanoalumina addition in Tech-sil25 maxillofacial silicone before and after exposure to artificial weathering conditions. Materials and Methods. A total of 144 samples were divided into four groups, a control group (n = 12) and three test groups, nanosilica (NS) (n = 36), nanoalumina (NA) (n = 36), and a hybrid nanoparticle (HySA) (n = 60) at different weight percentages (1, 2, and 3 wt. %) was added to Tech-sil25. Samples were exposed to artificial weathering for 100 hours, and subjected to characterizations involving tear strength, shore A hardness, roughness, and tensile strength tests. The data were analyzed using descriptive and inferential statistics using a one-way ANOVA test to determine the level of significance between the groups. Results. After 100 hours of artificial weathering, the one-way ANOVA result shows a highly significant increase in tensile and tear strengths with a minimal increase in hardness and roughness observed in samples containing 2% nanosilica (NS) followed by hybrid nanoparticle (HySA) of 1% nanoalumina (NA) + 1% nanosilica (NS) compared with a control group and other groups. Conclusions. The addition of nanosilica (NS), nanoalumina (NA), and a hybrid nanoparticle (HySA) to the Tech-sil25 maxillofacial silicone improved its mechanical properties. The combination of several filler reinforcements is essential for enhancing silicone’s antiaging properties of silicone and maintaining some of its mechanical properties to prolong the service life.